Pengaruh Penggunaan Sari Kluwek pada Pembuatan Bakpao Terhadap Kualitas Organoleptik - Bella Ariani Putri Amir; Ridawati Ridawati; Cucu Cahyana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The aim of this research was to analyze the effect of using kluwek juice on organoleptic quality of bakpao. This research used an experimental method, with the aim of obtaining the best bakpao formula with the addition of kluwek juice. In this research, experiments were carried out with different formulations, 7.5%, 10% and 12.5%. This research was carried out with the aim of determining the influence of Organoleptic Quality on the organoleptics quality of bakpao which includes aspects of pores, top surface, color, aroma, texture, sweetness and bitterness. The results of the organoleptic assessment, the percentage of kluwek juice was 7.5%, 10% and 12.5% regarding organoleptic quality in the aspects of pores, top surface, color, aroma, texture, sweetness and bitterness, there were no significant differences.